The somuncura large igneous province in Patagonia: Interaction of a transient mantle thermal anomaly with a subducting slab - Kay, S. Mahlburg (2007)
The Oligo-Miocene Somuncura province is the largest (∼55 000 km2) back-arc mafic volcanic field in Patagonia, and one of Earth's largest with no clear link to a hotspot or major extension. Major and trace element and Sr-Nd-Pb isotopic data suggest involvement of a plume-like component in the mantle magma source mixed with hydrous, but not high field strength element (HFSE)-depleted components, from a disintegrating subducting plate. Magmatism is attributed to mantle upwelling related to disturbances during plate reorganization, possibly at a time when the South America plate was nearly stationary over the underlying mantle. Melting was enhanced by hydration of the mantle during Paleogene subduction. Crustal contamination was minimal in a refractory crust that had been extensively melted in the Jurassic. Eruption began with low-volume intraplate alkaline mafic flows with depleted Nd-Sr isotopic signatures. These were followed by voluminous ∼29-25 Ma tholeiitic mafic flows with flat light and steep heavy rare earth element (REE) patterns, intraplate-like La/Ta ratios, arc-like Ba/La ratios and enriched Sr-Nd isotopic signatures. Their source can be explained by mixing EM1-Tristan da Cunha-like and depleted mantle components with subduction-related components. Post-plateau ∼24-17 Ma alkaline flows with steep REE patterns, high incompatible element abundances, and depleted Sr-Nd isotopic signatures mark the ebbing of the mantle upwelling.